Crystal structure of E-1-(2-hydroxyphenyl)-3-(3-hydroxyphenyl)-2-propen-1-one, C15H12O3 - M-C, Feng; MG, Tay; G-Y, Yeap; ΜM, Norani; SG, Teoh; Edward Richard, Tom Tiekink (Dgruyter Publisher, 1999)
Jump to ContentJump to Main Navigation: Log in; Register; Help; German; English; Take a Tour; Sign up for a free trial; Subscribe. OWV Logo. Search Advanced SearchHelp. My Content (1) Recently viewed (1). Crystal structure of E... My Searches (0). (0) Shopping Cart. Check Out. SUBJECTS: Architecture and Design; Area Studies; Arts; Chemistry; Classical and Ancient Near Eastern Studies; Computer Sciences; Cultural Studies; Economics; Engineering; Geosci